PERLINDUNGAN TERHADAP PENCARI SUAKA DAN PENGUNGSI MENURUT HUKUM ISLAM DAN HUKUM INTERNASIONAL (STUDI FILOSOFIS DAN ONTOLOGIS KEILMUAN): A Phylosophical and Ontolological Studies - Syahrin, Muhammad Alvi (Nurani, 2019)
The problem of refugees and the displacement of people in the country is the most difficult problem facing the world community today. Many discussions were held at the United Nations which continued to seek more effective ways to protect and assist these very vulnerable groups. Some people call for increased cooperation and coordination between aid agencies, others point to gaps in international regulations and call for further standards in this field. However, everyone agrees that this problem is a global and global problem. Therefore every approach and solution must be carried out comprehensively and explain all aspects of the problem from the causes of mass exodus to the elaboration of the necessary responses to overcome the range of problems of refugees from emergencies to repatriation. This study will discuss how the basic rules of protection for asylum seekers and refugees according to Islamic law and international law.